Longitudinal relations between parenting practices and prosocial behaviors in recent immigrant Latino/a adolescents: Familism values and ethnic identity as mediators - Maiya, Sahitya; Carlo, Gustavo; Davis, Alexandra N.; Schwartz, Seth J.; Unger, Jennifer B.; Zamboanga, Byron L.; Baezconde-Garbanati, Lourdes; Soto, Daniel W.; Lorenzo-Blanco, Elma I. (Frontiers in Developmental Psychology, 2024)
The present study investigated the mediating roles of familism values and ethnic identity in longitudinal associations between recent immigrant U.S. Latino/a adolescents' reports of their parents' (i.e., mothers' and fathers') use of social and material rewards and prosocial behaviors.Participants included 302 recent immigrant U.S. Latino/a adolescents (M age = 14.5 years at Time 1, range = 13-17 years, 53% male) recruited from Los Angeles and Miami. Participants self-reported on their perceptions of parents' use of social and material rewards (Time 1), familism values (Time 3), ethnic identity (Time 5), and multiple types of prosocial behaviors (Time 6). Path analyses showed that mothers' use of social rewards was indirectly related (via familism values and ethnic identity) to higher levels of everyday types of helping behaviors seen in youth, whereas mothers' use of material rewards was only directly related to motive-based helping behaviors. In contrast, we found no significant direct or indirect relations from fathers' use of social or material rewards and prosocial behaviors. The discussion describes the parenting and cultural assets that facilitate varied types and motives of prosocial behaviors in recent immigrant U.S. Latino/a youth. Family-based interventions, prosocial development theories, and future research on this topic can target prosocial parenting practices (e.g., social rewards) and cultural assets (e.g., familism values, ethnic identity) to facilitate helping in youth.